Polymorphisms in XPC, XPD and XPG DNA repair genes and leukemia risk in a Tunisian population. Issue 6 (June 2015) - Douzi, Kais; Ouerhani, Slah; Menif, Samia; Safra, Ines; Abbes, Salem
Abstract Human DNA repair mechanisms protect the genome from DNA damage caused by endogenous and environmental agents. Polymorphisms in DNA repair genes and differences in repair capacity between individuals have been widely reported in different cancers. In this study we aimed to evaluate the associations between XPC Lys939Gln (rs2228001), XPD Lys751Gln (rs13181) and XPG Asp1104His (rs17655) polymorphisms and leukemia risk in a Tunisian population. Genotypes were determined by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) in 206 patients with leukemia and 206 healthy controls. We found increased risk of leukemia among subjects carrying the XPC 939Gln/Gln genotype (odds ratio [OR] = 2.48, 95% confidence interval [CI] = 1.353–4.560, p = 0.0042). Moreover, in subgroup analysis according to clinical types, patients with chronic myeloid leukemia (CML) showed a higher risk than patients with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) (OR = 3.87, 95% CI = 1.820–8.237, p = 0.0003). However, the XPD 751Gln allele may be protective against CML and AML development, and no significant differences in genotype frequencies were observed for the XPG gene between patients and controls. Further studies with larger samples and risk factor information are needed.